Marketing strategies for Colombian artisans in international markets - Benavides, Laura Alejandra; Redondo, Andrea Carolina (Uptc, 2021)
The objective of this article is to propose alternatives for the marketing of products from the Colombian handicraft sector in international markets by identifying the Colombian handicraft sector and its participation in those markets. This preliminary study will allow strategies that would enhance the handicraft sector to be established. A non-experimental, descriptive, and documentary style methodological design was used. As a result, it was found that artisans have issues such as a lack of financial resources for the implementation of new technologies and training to fully understand the current market and its future interests. The study found that in order for artisans to have more opportunities to enter international markets and strengthen the sector, they must innovate, participate in events with fewer requirements, and create a company to have greater opportunities.